2017
DOI: 10.1007/s13577-017-0171-0
|View full text |Cite
|
Sign up to set email alerts
|

Peroxidatic cysteine residue of peroxiredoxin 2 separated from human red blood cells treated by tert-butyl hydroperoxide is hyperoxidized into sulfinic and sulfonic acids

Abstract: Peroxiredoxin 2 (Prx2) is a redox enzyme that is abundantly expressed in red blood cells (RBCs) and has been the focus of clinical attention for monitoring the oxidative status. We previously developed a method to quantify the reduced and hyperoxidized forms of Prx2 in human RBCs using reverse-phase high-performance liquid chromatography (HPLC). In the present study, we investigated the hyperoxidative status of Prx2 at the molecular level in a post-translational modification analysis using a liquid chromatogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…At higher levels of ROS, sulfenic acid undergoes further oxidation to sulfinic (-SO 2 H) or sulfonic (-SO 3 H) acid. Unlike sulfenic modification, sulfinic or sulfonic moieties are irreversible modifications, resulting in permanent damage of the protein, and are considered, in addition to protein carbonylation, markers of oxidative stress. , Interestingly, the above-described biochemical mechanisms enacted by ROS, in relation to their concentration, can produce a reversible modification of the function of a protein or induce an irreversible inactivation.…”
Section: Role Of the Intracellular Redox State In The Control Of Phys...mentioning
confidence: 99%
“…At higher levels of ROS, sulfenic acid undergoes further oxidation to sulfinic (-SO 2 H) or sulfonic (-SO 3 H) acid. Unlike sulfenic modification, sulfinic or sulfonic moieties are irreversible modifications, resulting in permanent damage of the protein, and are considered, in addition to protein carbonylation, markers of oxidative stress. , Interestingly, the above-described biochemical mechanisms enacted by ROS, in relation to their concentration, can produce a reversible modification of the function of a protein or induce an irreversible inactivation.…”
Section: Role Of the Intracellular Redox State In The Control Of Phys...mentioning
confidence: 99%
“…We previously established a method for the separation and detection of Prx2-SO 2/3 and reduced Prx2 [ 18 , 25 ]. Our method revealed that more hyperoxidized Prx2-SO 3 eluted faster than reduced Prx2.…”
Section: Discussionmentioning
confidence: 99%
“…The protein bands of interest were excised and subjected to in-gel digestion for mass spectrometric analysis as described previously 18,19) . The gel pieces were then destained, reduced with dithiothreitol, alkylated with iodoacetamide, and incubated in digestion buffer [50 mM NH4HCO3, 2 μM trypsin (Trypsin Gold; Promega, Madison, WI, USA) and 0.…”
Section: Identification Of Heparin-binding Proteinsmentioning
confidence: 99%